2019
DOI: 10.1080/20013078.2019.1585163
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals procoagulant properties of cigarette smoke‐induced extracellular vesicles

Abstract: Airway epithelial cells secrete extracellular vesicles (EVs) under basal conditions and when exposed to cigarette smoke extract (CSE). Getting insights into the composition of these EVs will help unravel their functions in homeostasis and smoking-induced pathology. Here, we characterized the proteomic composition of basal and CSE-induced airway epithelial EVs. BEAS-2B cells were left unexposed or exposed to 1% CSE for 24 h, followed by EV isolation using ultrafiltration and size exclusion chromatography. Isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…However, very few studies have analyzed the RNA cargo of EVs generated after ETS. Recently, Stassen and his group showed that tissue factor procoagulants are released from bronchial epithelial cells in response to contact with cigarette smoke extract through an EVs mechanism, suggesting a possible function of EVs after smoke exposure [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have analyzed the RNA cargo of EVs generated after ETS. Recently, Stassen and his group showed that tissue factor procoagulants are released from bronchial epithelial cells in response to contact with cigarette smoke extract through an EVs mechanism, suggesting a possible function of EVs after smoke exposure [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that cigarette smoke extract (CSE) increases the amount of small (80-250 nm) CD63 + CD81 + EVs released by bronchial epithelial cells [18]. These CSE-induced EVs were enriched in tissue factor (TF) compared to EVs secreted by unexposed cells [23]. Thus, they likely reflect epithelial activation and damage.…”
Section: Introductionmentioning
confidence: 99%
“…EV proteins have also been associated with CVD risk factors, such as smoking and obesity. In an in vitro study with bronchial epithelium cells, EVs derived from epithelial cells that were exposed to cigarette smoke extract were shown to contain higher levels of pro-coagulant proteins, including tissue factor [83]. In fact, EVs present in human blood contain several coagulation-related proteins and therefore, may contribute to the increased risk of a thrombotic event resulting in MI or stroke [24,43,84].…”
Section: Extracellular Vesicle Contents In Cvdmentioning
confidence: 99%